Target—effector interaction in the natural killer cell system: Isolation of target structures - John Roder; Anders Rosén; Éva Mária Fenyõ; Frederic A. Troy (1979)
A sensitive target binding assay has recently been shown to detect natural killer (NK) cells in the mouse. Preincubation of NK cells with detergent-solubilized cell-surface proteins of YAC lymphoma cells prevented subsequent binding to intact YAC targets. The NK target structures (NK-TS) consisted of three molecular species tentatively assigned molecular weights of 130,000, 160,000, and 240,000 based on electrophoretic mobility in sodium dodecyl sulfate/polyacrylamide gels. Moloney cell surface antigen (MCSA), gp71, p30, H-2, and NK-TS were localized in distinct fractions of gels. The NK-TS bound to concanavalin A-Sepharose columns and could be eluted with the specific sugar, suggesting that the target structures may be glycosylated. NK-TS molecules could not be detected in gels of NK-insensitive target cells such as P815, A9HT, YWA, or EL-4. The quantity obtained from the gels varied directly with the NK sensitivity of YAC which is more sensitive when grown in vitro than when grown in vivo . The NK-TS molecules specifically inhibited the binding of NK cells but not alloimmune T cells to their appropriate targets. Additional NK-sensitive tumor cells also expressed some or all of the target molecules exhibited by YAC. Some of these structures shared specificities in the case of MPC-11 or were unique in the case of Molt-4 and K562, as shown by cross-inhibition studies. These results suggest that NK-sensitive cell lines express distinct target structures with possible relevance to natural tumor resistance.